Tourism as a Tool: Rehumanizing Rio de Janeiro’s South Zone Favelas Through Community-Based Tourism Narratives - Van Rompu, Phie (Universidad del Pacífico, 2019)
This article proposes a conceptual framework for community-based tourism in Rio de Janeiro’s South Zone favelas that benefits these communities. It sheds light on how local guides use tourism as a tool to counter the prevailing negative perception of favelas and how these guides seek to rehumanize the favela by providing an alternative cultural narrative that challenges existing stereotypes, making these tours a form of everyday resistance. The article covers the material impact of these tours by highlighting tourists’ perceptions before and after visiting a favela and including the opinion of local favela residents about these tours.